DAMPAK PROGRAM BANK SAMPAH TERHADAP SOSIAL EKONOMI MASYARAKAT DI KELURAHAN BINJAI, KECAMATAN MEDAN DENAI, KOTA MEDAN - MITA Novianty (Welfare StatE, 2013)
One of the major breakthroughs in the management of waste in Indonesia is a waste bank program . Through this program , the paradigm established in the public mind that garbage is something that is useless and thrown away , changed into something that also has value and price . Bank through the garbage , people can save rubbish , which was then in a period of time can make money . Research studies using quantitative descriptive analysis . This study aims to determine how the programs socio-economic impact on the waste bank in the Kelurahan Binjai, Kecamatan Medan Denai . Impact is defined as a result of the influence that brings both positive and negative . In this case the intended impact on the socio-economic life of the people in the Kelurahan Binjai , Kecamatan Medan Denai. Based on the analysis of data disimpulakn that the existence of a positive impact on the socio-economic life of the people in the village after the construction of Binjai Garbage Bank . This is shown by the increase in people's income even though in few but provide significant benefits for society . Not only are revenues have increased , but health , and better social interaction among people are also the most important is a cleaner environment also increased over time . Keywords : Impact , Social Economy , Bank Garbage